Two-Years Corneal Collagen Cross-Linking Outcomes in Patients with Keratoconus (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aims: This study aimed to report refractive, topographic, and tomographic outcomes of 2-years cornealcollagen cross-linking in patients with progressive keratoconus.Materials and Method: This prospective study was conducted on76 eyes of 40 patients with progressivekeratoconus and a corneal thickness of at least 400?m. After the baseline examination, cross-linking wasperformed using riboflavin 0.1% and ultraviolet irradiation (370 nm, 3 mW/cm2) for 30 min. Uncorrectedvisual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), manifest refraction sphericalequivalent (MRSE), cylinder, keratometric readings, and corneal thickness were evaluated at baseline, 6,12, and 24 months after corneal collagen cross-linking.Results: Results showed that at a 24-month follow-up, mean BSCVA, and UCVA had significantimprovements. Changes in MRSE and cylinder were not significant during the two years of follow-up.At a 2-years follow-up, the mean values of minimum keratometry, maximum keratometry, and averagekeratometry decreased significantly to0.75, 0.97, and 0.52 D, respectively, compared to their baseline values.Anterior best fit sphere (BFS) also had significant difference at 24-month follow-up compared to base lineevaluation. The central corneal thickness decreased significantly up to38 ? after 2 years.Conclusion: Corneal collagen cross-linking is an effective treatment to stop the progression of keratoconusasshown by reduced keratometry and improved vision.